2023
DOI: 10.18632/aging.204904
|View full text |Cite
|
Sign up to set email alerts
|

Non-SMC condensin I complex subunit D2 (NCAPD2) reveals its prognostic and immunologic features in human cancers

Abstract: Non-SMC condensin I complex subunit D2 (NCAPD2) is overexpressed in some malignant tumors. However, there are few studies on the function of NCAPD2 in pan-cancer. We used the Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), Human Protein Atlas (HPA), and UALCAN to analyze NCAPD2 expression and promoter methylation levels in 33 tumors and normal samples. We performed immunohistochemistry (IHC) on liver cancer and corresponding normal tissues to examine NCAPD2 protein expression in LIHC. Kaplan-Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Currently, there is a growing acknowledgment of the pivotal role played by the immune system in the progression of tumors [44]. Multiple studies have shown that NCAPD2 impacts immune cell infiltration in various tumors, nevertheless, its precise role in LUAD remains uncertain [23]. Therefore, our study delves into the intricate relationship between NCAPD2 and immune cell infiltration, utilizing the CIBERSORT algorithm and validating our findings through the TIMER database.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Currently, there is a growing acknowledgment of the pivotal role played by the immune system in the progression of tumors [44]. Multiple studies have shown that NCAPD2 impacts immune cell infiltration in various tumors, nevertheless, its precise role in LUAD remains uncertain [23]. Therefore, our study delves into the intricate relationship between NCAPD2 and immune cell infiltration, utilizing the CIBERSORT algorithm and validating our findings through the TIMER database.…”
Section: Discussionmentioning
confidence: 74%
“…NCAPD2 assumes the role of a non-SMC subunit in condensin I, influencing the function of another non-SMC subunit of condensin I, sister chromatid separation, and chromosome alignment during metaphase [12]. Although previous studies have hinted at a potential connection between NCAPD2 and the prognosis of LUAD, its precise function and underlying molecular mechanisms remain elusive [23]. The objective of this research was to clarify the involvement of NCAPD2 in the progression of LUAD, with the intention of identifying a new potential prognostic biomarker and treatment targe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 6 NCAP family genes, including NCAPG, NCAPG2, NCAPH, NCAPH2, NCAPD2, and NCAPD3, recent studies have highlighted their possible significance in various clinical disorders. 23 - 25 …”
Section: Discussionmentioning
confidence: 99%